Free vibration of thick composite plates on non-homogeneous elastic foundations by dynamic stiffness method - Cuong, Nguyen Manh; Thinh, Tran Ich; Hien, Ta Thi; Ninh, Dinh Gia (Vietnam Journal of Mechanics, 2013)
This research presents a new model for vibration analysis of thick laminated plates on a non-homogeneous elastic foundation by the Dynamic Stiffness Method(DSM). The non-homogeneous foundation consists of multi-segment Winkler-type and Pasternak-type elastic foundation. The Dynamic Stiffness Matrices using the First ShearDeformation Theory (FSDT) are constructed for cross-ply thick composite plates. A computer program is written using the present formulation for calculating natural frequencies and harmonic response of composite plates subjected to various types of boundary conditions. Numerical results are validated by comparison with available results in the literature and with Finite Element Method (FEM). Different test cases make evidence the advantages of the present model: higher precision, less data storage, less computing time and studied frequency range extended.